Simulation study on the thermal effect of continuous laser heating quartz materials - Li, Wei; Wu, Jichuan; Li, Yanglong; Wu, Lingyuan; Fu, Bo (Frontiers in Chemistry, 2024)
The continuous development and application of laser technology, and the increasing energy and power of laser output have promoted the development of various types of laser optical systems. The optical components based on quartz materials are key components of high-power laser systems, and their quality directly affects the load capacity of the system. Due to the photothermal effect when the laser interacts with the quartz material and generates extremely high temperatures in a short period of time, it is impossible to experimentally solve the phenomena and physical mechanisms under extreme conditions. Therefore, it is very important to select a suitable method to investigate the thermal effect of intense laser interaction with quartz materials and explain the related physical mechanism. In this study, a threedimensional quarter-symmetric laser heating quartz material geometry model by using nonlinear transient finite element method was established, and its transient temperature field distribution of the quartz material after being heated by a 1064 nm continuous laser was investigated. In addition, the influence of different laser parameters (laser spot radius, heat flux and irradiation time), material parameters (material thickness, material absorption rate of laser) on the thermal effect of heating quartz material were also studied. When the laser heat flux is 20 W/cm 2 , the diameter of the laser spot is 10 cm, the irradiation time is 600 s and the thickness is 4 cm, the temperature after laser heating can reach 940.18 ℃, which is far lower than the melting point. In addition, the temperature maximum probes were set at the overall model, spot edge and rear surface respectively, and their temperature rise curves with time were obtained. It is also found that there is a significant hysteresis period for the rear surface temperature change of the quartz material compared with the overall temperature change due to heat conduction. Finally, the method proposed can also be applied to the laser heating of other non-transparent materials.